Emotional State and Feedback-Related Negativity Induced by Positive, Negative, and Combined Reinforcement - Xu, Shuyuan; Sun, Yuyan; Huang, Min; Huang, Yanhong; Han, Jing; Tang, Xuemei; Ren, Wei (Frontiers in Psychology, 2021)
Reinforcement learning relies on the reward prediction error (RPE) signals conveyed by the midbrain dopamine system. Previous studies showed that dopamine plays an important role in both positive and negative reinforcement. However, whether various reinforcement processes will induce distinct learning signals is still unclear. In a probabilistic learning task, we examined RPE signals in different reinforcement types using an electrophysiology index, namely the feedback-related negativity (FRN). Ninety-four participants were randomly assigned into four groups: base (no money incentive), positive reinforcement (presentation of money reward), negative reinforcement (removal of money losses), and combined reinforcement (money reward and removal of money loss) groups. In addition, in order to evaluate the engagement of emotional activity in the different reinforcement processes, Positive and Negative Affect Schedule-Expanded Form (PANAS-X) scales were applied before and after the experiment to detect the emotional changes. The results showed that there was no difference between groups in the dopamine-related learning bias. However, compared to the other three groups, negative reinforcement elicited smaller FRN (the difference-wave measure) during the learning, stronger positive affect and joviality and less fatigue after the learning, in which the difference between the negative and positive reinforcement group was smaller. The results indicated that pure avoidance motivation may induce distinct emotional fluctuations, which influences the feedback processing.